Agricultural Management Options for Climate Variability and Change: High-Residue Cover Crops - Joel Love; Jed Dillard; Kirk Brock; Daniel Dourte; Clyde Fraisse (EDIS)
While decision making in agriculture involves many aspects beyond climate, including economics, social factors, and policy considerations, climate-related risks are a primary source of yield and income variability. This 4-page fact sheet focuses on the use of high-biomass winter cover crops to improve production systems. Written by Joel Love, Jed Dillard, Kirk Brock, Daniel Dourte, and Clyde Fraisse, and published by the UF Department of Agricultural and Biological Engineering, August 2012.